Why people fail : the 16 obstacles to success and how you can overcome them - Reynolds, Siimon (San Francisco, CA : Jossey-Bass, 2012)
'An essential guide for mastering failure in order to achieve your goalsSuccess is often just a moment--a goal fulfilled, soon to be replaced with new goals. But failure is the ambitious person's constant companion, often dogging us for months, years or even decades before we finally reach our aim. In the groundbreaking book Why People Fail, Siimon Reynolds, one of the world's most successful entrepreneurs, explores the main causes of failure, in any field, and reveals solutions for overcoming them and creating a successful personal and professional life. Why People Fail offers strategies and ideas for defeating the sixteen most common failure habits such as destructive thinking, low productivity, stress, fixed mindset, lack of daily rituals, and more. Outlines the common habits that lead to failure and shows how to overcome them Features dozens of tips and exercises to help increase business and personal success Written by Siimon Reynolds, an internationally recognized expert on high performance and business excellence Many people have changed their lives by mastering just one of the timeless principles in this book. Master five or ten and your life will rocket to a totally new level'--Provided by publisher.
Includes bibliographical references.
Keywords: Failure (Psychology).; Success -- Psychological aspects